Genetic Variation in FABP4 and Evaluation of Its Effects on Beef Cattle Fat Content - Goszczynski, Daniel Estanislao (2017)
FABP4 is a protein primarily expressed in adipocytes and macrophages that plays a key role in fatty acid trafficking and lipid hydrolysis. FABP4 gene polymorphisms have been associated with meat quality traits in cattle, mostly in Asian breeds under feedlot conditions. The objectives of this work were to characterize FABP4 genetic variation in several worldwide cattle breeds and evaluate possible genotype effects on fat content in a pasture-fed crossbred (Angus-Hereford-Limousin) population. We re-sequenced 43 unrelated animals from nine cattle breeds (Angus, Brahman, Creole, Hereford, Holstein, Limousin, Nelore, Shorthorn, and Wagyu) and obtained 22 single nucleotide polymorphisms (SNPs) over 3,164 bp, including four novel polymorphisms. Haplotypes and linkage disequilibrium analyses showed a high variability. Five SNPs were selected to perform validation and association studies in our crossbred population. Four SNPs showed well-balanced allele frequencies (minor frequency > 0.159), and three showed no significant deviations from Hardy-Weinberg proportions. SNPs showed significant effects on backfat thickness and fatty acid composition (P < 0.05). The protein structure of one of the missense SNPs was analyzed to elucidate its possible effect on fat content in our studied population. Our results revealed a possible blockage of the fatty acid binding site by the missense mutation.